Formulation and Preparation of Telang Flower Kombucha Spray as a Pharmaceutical Biotechnology Product to Inhibit the Growth of Pathogenic Fungi for Horticultural Commodity Types of Shallots (Alliium cepa L) - Rezaldi, Firman; Ratna Fitry Yenny, Ratna Fitry Yenny; Sugiono Sugiono, Sugiono Sugiono; Maskun Kurniawan, Maskun Kurniawan; Ipul Saifullah, Ipul Saifullah; Rizal Rohmatulloh, Rizal Rohmatulloh; Misbakhul Munir, Misbakhul Munir; Vevi Maritha, Vevi Maritha; Novi Ayuwardani, Novi Ayuwardani; Barolym Tri Pamungkas, Barolym Tri Pamungkas (Agrotechnology Study Program, Faculty of Agriculture, Wijaya Kusuma Surabaya University, 2024)
In the form of natural aerosol formulations and preparations, butterfly pea flower kombucha in the form of waste can be utilized as a pharmaceutical biotechnology product to inhibit the growth of pathogenic fungi that cause disease or infection in horticultural commodity plants. Horticultural commodity plants are plant commodities that have the potential to be developed as food flavorings, traditional medicines, and spices, especially in the shallot species Allium cepa L. One of the obstacles to the growth and development of shallot plants is being hampered by attacks by pathogenic fungi from the species Fusarium fujikuroi, Alternaria sp, and Colletotrichum gloeosporioides. A safe and environmentally friendly solution to prevent the growth of these three pathogenic fungi is to utilize the fermentation waste of butterfly pea flower kombucha as a pharmaceutical biotechnology product in the form of natural spray formulations and preparations with concentrations of 20%, 30%, and 40%. Based on the one-way ANOVA test with each P value <0.05, supported by post hoc analysis. Specifically, the 40% formula differs significantly from the 20% and 30% formulas as a pharmaceutical biotechnology product in its ability to inhibit the growth of the three pathogenic fungi in shallot plants, and is the most optimal formula.